Beneficial owner of interests, abuse of rights and free movement of capitals: by purpose of The Judgment Of The Court 26 February 2019 - López Espadafor, Carlos María; García Guerrero, David (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The Judgment Of The Court (Grand Chamber) 26 February 2019 can contribute useful tools to the Tax Administrations of the Member States when interpreting and applying European Union law in respect of exemption of interest and royalty payments which are satisfied by one entity to another one according to the Directive 2003/49. The key point is to determine if a company is a beneficial owner of the interests. This Judgment provides arrangements in which there is abuse of rights against the cases where the beneficial owner condition simply does not exist. It highlights certain situations in which the free movement of capital has been violated.